A facile synthesis of stable β-amino-N-/O-hemiacetals through a catalyst-free three-component Mannich-type reaction. Issue 15 (12th April 2017) - Abonia, Rodrigo; Castillo, Juan C.; Garay, Alexander; Insuasty, Braulio; Quiroga, Jairo; Nogueras, Manuel; Cobo, Justo; D'Vries, Richard
Graphical abstract: Highlights: A catalyst-free three-component Mannich-type reaction is proposed. Novel and stable β-amino- N -/ O -hemiacetals were obtained from this strategy. Reactions proceeded with the formation of iminium ions as the key intermediates. Single crystal X-ray analysis confirmed the structure and stability of the obtained compounds. Abstract: A practical, straightforward and one-step procedure for the synthesis of novel and stable β-amino- N -/ O -hemiacetals (i.e. γ-aminoalcohols) is provided. The title compounds were obtained in good to excellent yields through an uncatalyzed three-component reaction by treatment of secondary amines with polyformaldehyde and electron-rich alkenes in acetonitrile as solvent at ambient temperature. The reactions proceeded with the formation of iminium ions, through a Mannich-type reaction, as the key intermediates for the generation of the target products. Single crystal X-ray analysis of derivative4l confirmed unequivocally the structure and stability of the obtained compounds.